PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT.GLOBALINDO MUTIARA DI KABUPATEN KOTA TUAL, PROVINSI MALUKU - Leonardi Lokawati; Juarini Juarini; Daru Retnowati (Jurnal Dinamika Sosial Ekonomi, 2015)
This study aims to discover the extent of the influence of leadership style and work environment directly and indirectly on the motivation of employees and the impact of leadership style, work environment and motivation are directly and indirectly to the performance of employees in PT.Globalindo Mutiara. The basic method used in this research is descriptive method. The basic method used in this research is descriptive method , and the method of implementation of the research is the case study method. Respondents making method using census method, the number of respondents is 38 people. Kinds of data used are primary data and secondary data, with the data collection technique using a questionnaire, observation  and  interview  data  source  from  the  employee,  the  data company,  library materials, previous research and media internet.The analytical method used is path analysis. The results showed that the style of leadership and work environment directly affects motivation and indirectly by the leadership style through the work environment to motivate employees at PT.Globalindo Mutiara. Variable style of leadership, and motivational work environment directly affects employee performance and leadership style indirect effect on performance through motivation and indirectly by the work environment through motivation on employee performance in PT.Globalindo Mutiara.Keywords : Leadership style, work environment, motivation and performance of employees.